Cognitive changes in alcohol-induced psychotic disorder - Melany L. Hendricks; R. A. Emsley; D. G. Nel; H. B. Thornton; G. P. Jordaan (BMC Research Notes, 2017)
Abstract Aims This study aimed to explore the neuro-cognitive deficits of alcohol-induced psychotic disorder as compared to the cognitive deficits of uncomplicated alcohol dependence. Methods Participants were recruited from the acute psychiatric admission wards of the Department of Psychiatry, University of Stellenbosch and Stikland and Tygerberg Academic Hospitals in the Western-Cape, South Africa. Participants who met DSM IV TR criteria (American Psychiatric Association. Diagnostic and statistical manual of mental disorders. American Psychiatric Association, Washington, DC, 2000) for Alcohol Dependence and for alcohol-induced psychotic disorder, respectively, were included. Participants who met criteria for another current DSM IV TR Axis I disorder were excluded. A structured interview was done prior to neuropsychological assessment to ascertain current mental state and to obtain relevant demographic detail and history. Neuropsychological assessments were performed and supervised by clinical psychologists at either Tygerberg or Stikland Hospital. Results The groups were matched demographically with similar period of abstinence prior to assessment. The alcohol-induced psychotic disorder group experienced first psychotic symptoms at age 35. The results reflected statistically significant differences on tasks measuring immediate memory; recall upon delay; exaggeration of memory difficulty and abstract thinking. Conclusion This study concurs with earlier literature that some cognitive deficits are greater in alcohol-induced psychotic disorder compared to uncomplicated alcohol dependence.